Analisis Pengunaan Bahasa Indonesia pada Ruang Publik di Galaxy Mall Surabaya - Aulia Ramadhani; Nabila Dwi Rahma; Zahra Khania Putri; Arya Dany Ardhiansah; Alifah Almas Alwani (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This article discusses the use of Indonesian in public spaces, precisely at Galaxy Mall Surabaya. The purpose of this article is to find out the phenomena and factors related to these phenomena. Data collection was carried out in Surabaya in March 2023. Data was obtained by distributing questionnaires online using a purposive sampling non-random sampling technique. The results obtained from the research conducted show that the use of Indonesian in public spaces is lacking because many people or companies in malls often use foreign languages, more precisely, most of them use English.